Geo-Temporal Signatures of Physicochemical and Heavy Metals Pollution in Groundwater of Khulais Region—Makkah Province, Saudi Arabia - Khan, Mohd Yawar Ali; El Kashouty, Mohamed; Gusti, Waleed; Kumar, Amit; Subyani, Ali Mohammad; Alshehri, Ahmed (Frontiers in Environmental Science, 2022)
Seawater has intruded into many of Saudi Arabia’s Red Sea coastal aquifers, with varying degrees of extension depending on location, hydrogeology, and population density. This study aimed to evaluate and comprehend the processes that influence the hydrogeochemical characteristics of the coastal aquifer in Saudi Arabia’s Khulais region. Groundwater samples were taken from nineteen locations during the winter and summer of 2021, and data from major ions and trace elements were examined and interpreted using ArcGIS software. The total dissolved solids (TDS) concentrations ranged between 480 and 15,236 mg/L and 887–18,620 mg/L in winter and summer, respectively. Groundwater TDS concentration was observed to be influenced by groundwater flow, lithogenic, anthropogenic, and seawater intrusion in this study (2021) when compared to 2016. The concentration of nitrate (NO3−) and strontium (Sr) in most samples exceeds the drinking guidelines. The occurrence of high concentrations of bromide (Br), Fluoride (F), Iron (Fe) (winter and summer) and Aluminum (Al), Boron (B), Chromium (Cr), Nickel (Ni), lead (Pb), cadmium (Cd), cobalt (Co), copper (Cu) and manganese (Mn) (winter) was also exhibited and observed up to more than drinking and irrigation limits. The central part of the study area was affected by seawater intrusion. The hydraulic conductivity of the topsoil was measured, and it ranged from 0.24 to 29.3 m/day. Based on electrical conductivity (EC) and sodium absorption ratio, most aquifer samples were unsuitable for irrigation (SAR).